The legacy of killing dragon in Kurdish literature - Hassan, Farhad (Humanities Journal of University of Zakho, 2022)
Killing dragon has a vital position in nations’ myth and it is classified as ancient legacies of champions. The oldest Kurdish tale about killing dragon has been narrated in the book of Avesta. In different sections of the book, heroic role of Kirsāsp (Kərəsāspa) which was known as dragon killer has been mentioned. His legacy and champ tales which is full of daring and bravery has been narrated, through Kurdish language, in Avestan text. In parallel with Avesta, a part of the battles has been narrated in Pahlavi books and through those narration, vague parts of Avestan narration could be completed. The current research, through myths analysis, has tried to collect the data about the different sections of Kirsāsp myth, the dragon killer, in Avestan and Pahlavi texts and analyses them. The finding shows that the oldest dragon killing myth in Kurdish verbal literature, that sourced from ancient Kurdish religious and national beliefs, was written in Avestan book.